2007
DOI: 10.1002/gps.1884
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of knowledge and beliefs about depression among long‐term care staff

Abstract: Educational interventions about depression should be specifically geared to meet the needs of paraprofessional caregivers who provide the majority of care to LTC residents, yet possess less knowledge about depression and its treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 23 publications
3
31
2
1
Order By: Relevance
“…In the medical records, we found doctors' notes regarding depression in 40% and nurses' notes in 47% of those depressed. Even though the nurses pay more attention to patients' depressive symptoms, their accuracy in diagnostics is limited [32,33]. We can only speculate about the reasons for the doctors' diagnostic inaction.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical records, we found doctors' notes regarding depression in 40% and nurses' notes in 47% of those depressed. Even though the nurses pay more attention to patients' depressive symptoms, their accuracy in diagnostics is limited [32,33]. We can only speculate about the reasons for the doctors' diagnostic inaction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in stark contrast to older adults’ expressed preference for non-pharmacological interventions (Unutzer et al, 2003) and the availability of psychosocial interventions that may be used in daily care (Mellor et al, 2010; Smith, Johnson, Seydel, & Buckwalter, 2010). Common deterrents to quality depression care in NHs include staff’s lack of knowledge about depression signs and symptoms, lack of familiarity with psychosocial or medication interventions, beliefs that older adults don’t want to talk about their feelings, and perceptions that their primary focus should be on physical care tasks (Ayalon, Arean, & Bornfeld, 2008; Davison, et al, 2009). In summary, many opportunities exist to reduce disability and improve quality of life for depressed older adults by enhancing depression knowledge and skills through training.…”
mentioning
confidence: 99%
“…Other studies [21] have shown that nurses are no better at identifying depression than other staff members. In addition, length of service has also been shown to be unrelated to level of knowledge about depression [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have looked at staff training in depression recognition [26-28]; staff knowledge of depression [23,29] and confidence in managing depression [22,25]; to our knowledge, no other studies have explored unprompted knowledge of appropriate help giving behaviours or examined staff confidence in knowing how to respond to depression in high care environments. For this reason, the present study aims to extend previous research by focusing on staff self-efficacy and knowledge of appropriate help giving responses and their likelihood of providing assistance to potentially depressed care recipients.…”
Section: Introductionmentioning
confidence: 99%